Interactions in interpretation : the pilgrimage of meaning through biblical texts and contexts - Roskovec, Jan, 1966-; Hušek, Vít (Brill, 2021)
"The concept of intertextuality was originally coined as an instrument in answering the question of how meaning is communicated through texts. The Interactions in Interpretation discusses various aspects of how the world of the Bible (seen as a world of a certain language: a complex of ideas, notions, images, idioms, stories, that are shared and referred to) communicates with other worlds in both directions. The collection of studies follows three types of interactions with marked bearing on understanding: (1) interactions with a particular motif of dream, (2) interactions with a particular text of Isa 6:9-10, (3) intertextuality in changing contexts"--